Comparing the effects of three different multilayer dressings for pressure ulcer prevention on sacral skin after prolonged loading: An exploratory crossover trial. Issue 2 (21st December 2020) - Lechner, Anna; Rancan, Fiorenza; Hadam, Sabrina; Vogt, Annika; Blume‐Peytavi, Ulrike; Kottner, Jan
Abstract: Evidence suggests that preventive dressings applied on sacral skin help to prevent pressure ulcers. However, possible performance differences of different dressing types are unclear. An exploratory randomized crossover trial with intra‐individual comparisons was conducted to compare the effects of three different multi‐layer foam dressings (Mepilex Border Sacrum, ALLEVYN Life Sacrum and Optifoam Gentle Sacrum) compared to no dressing on the sacral skin. Healthy female volunteers (n = 12, mean age 72 years) wore three different dressings on their sacral skin for 3.5 hours while lying supine on a standard hospital mattress. At regular intervals, subjects performed standardized movements to enhance shear loads. Skin surface temperature, stratum corneum hydration, erythema, skin roughness and the interleukin 1 alpha (IL‐1α) concentration per total protein were measured at baseline and after the lying periods. After 3.5 hours, the median skin temperature increased in all four groups between 3.0°C and 3.8°C with only minor differences between the no dressing and the dressing groups. Median stratum corneum hydration increased during the lying period in all groups with highest increases in the Optifoam Gentle Sacrum (7.3 arbitrary units) and no dressing group (7.0 arbitrary units). There was a median decrease of the mean roughness (Rz) in the Optifoam Gentle Sacrum group of −6.3 μm but no relevant changes in the other groups. After loading, the erythema index was highest in the ALLEVYN Life Sacrum and no dressing groups. Highest releases of IL‐1α were observed in the ALLEVYN Life Sacrum and Optifoam Gentle Sacrum groups, in the Mepilex Border Sacrum group changes were minor. Study results indicate, that the application of preventive dressings on sacral skin during loading do not cause additional occlusion compared to loading without dressings when lying supine. Different dressings cause different cutaneous responses during loading.